Myosin Vb is required for correct trafficking of N‐cadherin and cardiac chamber ballooning. Issue 4 (19th March 2019) - Grassini, Daniela R.; da Silva, Jason; Hall, Thomas E.; Baillie, Gregory J.; Simons, Cas; Parton, Robert G.; Hogan, Benjamin M.; Smith, Kelly A.
Abstract : Background: During heart morphogenesis, the cardiac chambers undergo ballooning: a process involving regionalized elongation of cardiomyocytes. Cardiomyocyte shape changes require reorganization of the actin cytoskeleton; however, the genetic regulation of this process is not well understood. Results: From a forward genetic screen, we identified the zebrafish uq 23ks mutant which manifests chamber ballooning defects. Whole‐genome sequencing‐mapping identified a truncating mutation in the gene, myo5b. myo5b encodes an atypical myosin required for endosome recycling and, consistent with this, increased vesicles were observed in myo5b mutant cardiomyocytes. Expression of RFP‐Rab11a (a recycling endosome marker) confirmed increased recycling endosomes in cardiomyocytes of myo5b mutants. To investigate potential cargo of MyoVb‐associated vesicles, we examined the adherens junction protein, N‐cadherin. N‐cadherin appeared mispatterned at cell junctions, and an increase in the number of intracellular particles was also apparent. Co‐localization with RFP‐Rab11a confirmed increased N‐cadherin‐positive recycling endosomes, demonstrating N‐cadherin trafficking is perturbed in myo5b mutants. Finally, phalloidin staining showed disorganized F‐actin in myo5b cardiomyocytes, suggesting the cytoskeleton fails to remodel, obstructing chamber ballooning. Conclusions: MyoVb is required for cardiomyocyte endosomal recycling and appropriate N‐cadherin localization during the onset of chamber ballooning. Cardiomyocytes lacking MyoVb are unable to reorganize their actin cytoskeleton, resulting in failed chamber ballooning. Developmental Dynamics 248:284–295, 2019. © 2019 Wiley Periodicals, Inc. Key Findings: Mutation of the atypical myosin gene, myo5b, causes cardiac chamber defects in zebrafish. MyoVb is required for endosomal recycling and myo5b mutants have increased recycling endosomes in their cardiomyocytes. N‐cadherin, the major cadherin of cardiomyocytes, is mislocalised in uq23ks mutants and co‐localisation in recycling endosomes is increased in mutant cardiomyocytes. F‐actin reorganisation does not take place in mutant cells. This correlates with altered cell morphology, explaining the basis of the morphogenesis defect of the cardiac chambers.